Kerja Sama Jakarta-New South Wales dalam Kerangka Paradiplomasi melalui IA-CEPA - Saepudin, Saepudin; Ibrahim, Budiman; Aisyah Putri, Dheeva Maurellya; Amira, Naila Safa (Universitas Al-azhar Indonesia, 2024)
The Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) is the most comprehensive trade relationship agreement Indonesia has, covering aspects such as tariff elimination, trade facilitation, investment, downstream and economic cooperation between Indonesia and Australia. Implementing the IA-CEPA involves many actors, from business to sub-national governments, which are trying to open markets, expand business, and increase investment. Therefore, this research aims to examine the prospects of sub-national collaboration in various sectors, such as education, tourism, economy and digital business, especially between Jakarta and New South Wales. This research uses a descriptive qualitative method with sucondary data collection techniques through, books, journal articles, website articles, or with previous research. The concepts of paradiplomacy and bilateral relations are used as analytical tools in this research. By using this concept, this research concludes that the existence of sub-national IA-CEPA between the two countries has sufficient space to establish and strengthen cooperation, one of which is the sister state province cooperation between Jakarta and New South Wales by focusing on economic sustainability efforts, which has the potential to realize Jakarta's big vision as a global business city after it is no longer the capital of Indonesia.Keywords: Global City, IA-CEPA, Jakarta, New South Wales, Sister Province